Experience with the use of glucocorticosteroid implants in patients with macular edema associated with sarcoidosis. - V.A. Pavlov; E.V. Kryukov; D.V. Davydov; A.A. Zaytsev; V.E. Kurnosov (Офтальмохирургия)
Purpose. To evaluate the results of treatment of patients with sarcoidosis with chronic non-infectious uveitis complicated by macular edema by intravitreal injection of a glucocorticosteroid implant with previously used methods. Material and methods. The study performed a comparative analysis of data from patients with cystic macular edema against the background of chronic non-infectious uveitis associated with sarcoidosis, with corrected visual acuity of more than 0.05 (according to the Golovin-Sivtsev table). Group 1 (prospective analysis) included the results of treatment of patients with sarcoidosis with corticosteroid implants (4 eyes, 4 patients). In the 2nd group (retrospective analysis of the medical history), patients underwent peribulbar administration of betamethasone (9 eyes, 7 patients). The parameters were analyzed after 2.0±0.5, 4.0±0.5 and 6.0±0.5 months with assessment of maximally corrected visual acuity (BCVA), OCT, color photography, and IOP control. The risk of recurrence of macular edema when comparing groups was assessed over a 6-month follow-up period. Results. During the observed period in both groups, no complications were detected in any case. According to visometry and OCT, the best functional results were obtained in group 1. Average visual acuity after 6 months. was 0.7±0.1, the thickness of the retina in the central zone was 331±15 μm. Conclusion.According to the results of the study, it was found that intravitreal injection of dexamethasone implant in its effectiveness surpasses the previously used peribulbar injections of betamethasone in terms of the quality of restoration of visual functions, the effectiveness of reducing macular edema and the duration of remission of the chronic inflammatory process.